Effect of Using the Financial Information Technology System (SANAMA: Real-time Monitoring System of the Department of Financial Monitoring and National Treasury) on the Transparency, Accountability, and Audit of the National Budget Statement - Ahmad Barani (Journal of Global Pharma Technology, 2017)
The aim of this study was to investigate the effect of financial information technology system (SANAMA: real-time monitoring system of the Department of Financial Monitoring and National Treasury) on the transparency, accountability, and audit of the national budget performance statement. This system improves management of the financial system in the area of resource consumption and national budget through a continuous financial control and supervision of the public resources consumption. The lack of timely and quick access to information and audit data resulting from traditional implementation of affairs reduces the accuracy and quality of the audits in addition to increasing the cost and time. Accordingly, the Ministry of Economic Affairs and Finance launched an electronic surveillance system known as the